The Fabrication of Alginate and Curcumin Biocomposite Film for Wound Healing Applications - Razak, Nur Afiqah Adyani; Idris, Maizlinda Izwana (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Wound healing is an arduous and dynamic process to regenerate the debilitated tissue integrity. In this study, a biocomposite film of alginate andcurcumin was fabricated using solution casting method. The physicochemical and antibacterial properties of the films were investigated. The films were fabricated with 0.2%, 0.4%, 0.6%, 0.8% and 1.0% of curcumin concentrations and they were characterized using the digital micrometer, Fourier transform infrared spectroscopy (FTIR), goniometer and atomic force microscope (AFM) and the antibacterial assay was done using disc diffusion method. The value of the thickness and the surface roughness from AFM findings increased with the increased concentration of curcumin. It was found, the successful intermolecular interactions between curcumin and alginate were also visible in the film's FTIR spectrum. Next, the contact angle measurement also exhibits a similar pattern when value increased with the concentrations of curcumin as well. The antibacterial study on biocomposite film with S.aureus was evaluated. Unfortunately, it was found there is still no resistance on the bacterial growth on the samples. This may be due to the low concentration of curcumin applied or used in this study. Nevertheless, this biocomposite film could be possibly develop as a wound dressing with further improvements.